2021
DOI: 10.1371/journal.pone.0252370
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry in auditory multistability

Abstract: In multistability, a constant stimulus induces alternating perceptual interpretations. For many forms of visual multistability, the transition from one interpretation to another (“perceptual switch”) is accompanied by a dilation of the pupil. Here we ask whether the same holds for auditory multistability, specifically auditory streaming. Two tones were played in alternation, yielding four distinct interpretations: the tones can be perceived as one integrated percept (single sound source), or as segregated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
(108 reference statements)
2
5
0
Order By: Relevance
“…The PD events rate (Figure 4b) as transient pupil changes were higher when perceptual alternation occurred, which is in line with the previous studies (Einhäuser et al, 2008; Grenzebach et al, 2021). As these transient PD and baseline pupil changes related to cognitive shift are thought to reflect the different LC firing patterns or neural pathways, event‐related changes in pupil size may be triggered by stimulus saliency or surprise upon perceptual transition (Kloosterman et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The PD events rate (Figure 4b) as transient pupil changes were higher when perceptual alternation occurred, which is in line with the previous studies (Einhäuser et al, 2008; Grenzebach et al, 2021). As these transient PD and baseline pupil changes related to cognitive shift are thought to reflect the different LC firing patterns or neural pathways, event‐related changes in pupil size may be triggered by stimulus saliency or surprise upon perceptual transition (Kloosterman et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…To compare by the within-subject design, the participants who were not rejected in both Experiments 1 and 2 were examined in the following analysis. Two-way repeated measures ANOVAs on the averaged PD events with the response content and experiment as within-subject factors revealed that the average number of PD events was larger in alternation trials than in notrials (F(1,18) = 5.973, p = .025, 2 p = 0.249, BF 10 = 2.186), consistent with the previous studies (Einhäuser et al, 2008;Grenzebach et al, 2021). The number of PD events was larger in Experiment 1 than in 2 (F(1,18) = 7.77, p = .012, 2 p = 0.302, BF 10 = 17.622), which could be explained by the higher task demand in Experiment 1, as the LC-NE system reflects a broad range of cognitive processes.…”
Section: Transient Pupil Dilation/constriction (Pd/pc)supporting
confidence: 90%
See 3 more Smart Citations